Marketing Strategies for Launching Water Soluble NPK Fertilizers - Deepa, D.N. (Indian Journal of Marketing, 2005)
The three major categories of fertilizer industry in India are Public Sector Undertaking s, Co-operatives and Private Sector. About 33 Major manufacturers have been producing N and NP/NPK fertilizers in the country. The fertilizer consumption depends upon the cropping pattern. Different types of fertilizers like straight fertilizers; complex fertilizers and mixed fertilizers are available in the market. Traditionally nutrients have been applied by either broadcasting or application of granular or complex fertilizers directly in the soil in bulk quantum. Over the years, in order to reduce cost and increase yield, farmers have been adopting alternative methods of application of fertilizers such as fertigation and foliar feeding. With the advent of drip and and sprinkler irrigation for water management, fertigation is gaining importance. Water-soluble NPK fertilizers are being used for different crops like vegetables and ornaments. It enhances the nutrient uptake and reduces the leaching loss of nutrients in soluble form. Water-soluble NPK fertilizers have been recommended for plants as a supplementary dose but it would be an additional cost to the farmers. Hence, it is essential to assess the farmers’ preference for using the same before launching the product for coffee plantations.